A program of family-centered care for adolescents in short-term stay groups of juvenile justice institutions - Inge Simons; Eva Mulder; René Breuk; Kees Mos; Henk Rigter; Lieke van Domburgh; Robert Vermeiren (BMC, 2017)
Abstract Background To provide successful treatment to detained adolescents, staff in juvenile justice institutions need to work in family-centered ways. As juvenile justice institutions struggled to involve parents in their child's treatment, we developed a program for family-centered care. Methods The program was developed in close collaboration with staff from the two juvenile justice institutions participating in the Dutch Academic Workplace Forensic Care for Youth. To achieve an attainable program, we chose a bottom-up approach in which ideas for family-centered care were detailed and discussed by workgroups consisting of group leaders, family therapists, psychologists, other staff, researchers, and a parent. Results The family-centered care program distinguishes four categories of parental participation: (a) informing parents, (b) parents meeting their child, (c) parents meeting staff, and (d) parents taking part in the treatment program. Additionally, the family-centered care program includes the option to start family therapy during detention of the youths, to be continued after discharge from the juvenile justice institutions. Training and coaching of staff are core components of the family-centered care program. Conclusions The combination of training and the identification of attainable ways for staff to promote parental involvement makes the family-centered care program valuable for practice. Because the program builds on suggestions from previous research and on the theoretical background of evidence-based family therapies, it has potential to improve care for detained adolescents and their parents. Further research is required to confirm if this assumption is correct.